Growth and juvenile development of Uca maracoani Latreille 1802-1803 in laboratory conditions (Crustacea, Decapoda, Brachyura, Ocypodidae) - Hirose, Gustavo Luis [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (My University, 2008)
The life cycle of decapod crustaceans can be classified into three distinct morphological phases: larval, juvenile and adult. Despite its recognized importance, studies of the juvenile phase have been neglected. The present study aimed to analyze the growth of juveniles from a single population of Uca maracoani under laboratory conditions, and also to describe the morphological differentiation of pleopods in each sex. Megalopae and juvenile crabs of U. maracoani obtained on a mud beach at Jabaquara, Paraty, on the southern coast of the state of Rio de Janeiro (Brazil), were reared in the laboratory. The specimens were checked daily for molts and deaths. The carapace widths (CW) of intact exuviae and dead individuals were measured under a stereoscopic microscope provided with a micrometer rule. These data allowed the definition of a growth equation as well as the stages related to the beginning of pleopod development, which begins when females reach 3.0 mm CW (6th juvenile developmental stage), similar to the sizes reported for other species of the genus. In males, however, pleopods appear when the crabs reach 3.5 mm CW, equivalent to the 7th developmental stage. This difference may be related to differential growth between sexes. It also may be a consequence of laboratory rearing, or may represent an actual feature of the species. © E. Schweizerbart'sche Verlagsbuchhandlung (Nägele u. Obermiller), 2008.
Keywords: Growth; Juvenile development; Ocypodidae; Sex differentiation; Uca maracoani